7y-(6x-3y)*4-3(x+y)=

Simple and best practice solution for 7y-(6x-3y)*4-3(x+y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-(6x-3y)*4-3(x+y)= equation:


Simplifying
7y + -1(6x + -3y) * 4 + -3(x + y) = 0

Reorder the terms for easier multiplication:
7y + -1 * 4(6x + -3y) + -3(x + y) = 0

Multiply -1 * 4
7y + -4(6x + -3y) + -3(x + y) = 0
7y + (6x * -4 + -3y * -4) + -3(x + y) = 0
7y + (-24x + 12y) + -3(x + y) = 0
7y + -24x + 12y + (x * -3 + y * -3) = 0
7y + -24x + 12y + (-3x + -3y) = 0

Reorder the terms:
-24x + -3x + 7y + 12y + -3y = 0

Combine like terms: -24x + -3x = -27x
-27x + 7y + 12y + -3y = 0

Combine like terms: 7y + 12y = 19y
-27x + 19y + -3y = 0

Combine like terms: 19y + -3y = 16y
-27x + 16y = 0

Solving
-27x + 16y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16y' to each side of the equation.
-27x + 16y + -16y = 0 + -16y

Combine like terms: 16y + -16y = 0
-27x + 0 = 0 + -16y
-27x = 0 + -16y
Remove the zero:
-27x = -16y

Divide each side by '-27'.
x = 0.5925925926y

Simplifying
x = 0.5925925926y

See similar equations:

| u/2-7=21 | | 27=2+5v | | .62*x=3998800 | | .62*x=3499200 | | .62*x=3500000 | | 6jk/2k | | .62*x=5500000 | | 2[6y+3]=3[2+4y] | | 3.2h-h^2=0.64 | | 9x-9=x-45 | | 3a-6=a-9 | | 108=x*12 | | -9x+2y=-78 | | 6x+7y=27 | | 9(2x+2)-6(2x+2)-1=0 | | (2x-3)(x-4)-18=0 | | 6x-100=10 | | n=IRE-Ir | | 69x-100=15 | | 20x^2-40x-16=0 | | 69x-1000=15 | | 3-5y/4=8 | | X^2+4X+480=0 | | 34x+1-2*32x+2+1=0 | | 6x^2-12x-6= | | a^4-8a^2-16a+24=0 | | x^2+y^2+10x+4y-3=0 | | r^2-16r+160=0 | | x^2+y^2-12x+6y-2=0 | | 9x^2+9y^2-12x+6y-2=0 | | 360/(x-4)=(360/x)-3 | | x-0.05x=160000 |

Equations solver categories